Unearthing the Polynesian past : explorations and adventures of an island archaeologist - Kirch, Patrick Vinton (University of Hawaiʻi Press, 2015)
Perhaps no scholar has done more to reveal the ancient history of Polynesia than noted archaeologist Patrick Vinton Kirch. For close to fifty years he explored the Pacific, as his work took him to more than two dozen islands spread across the ocean, from Mussau to Hawai'i to Easter Island. In this lively memoir, rich with personal-and often amusing-anecdotes, Kirch relates his many adventures while doing fieldwork on remote islands. At the age of thirteen, Kirch was accepted as a summer intern by the eccentric Bishop Museum zoologist Yoshio Kondo and was soon participating in archaeological digs on the islands of Hawai'i and Maui. He continued to apprentice with Kondo during his high school years at Punahou, and after obtaining his anthropology degree from the University of Pennsylvania, Kirch joined a Bishop Museum expedition to Anuta Island, where a traditional Polynesian culture still flourished. His appetite whetted by these adventures, Kirch went on to obtain his doctorate at Yale University with a study of the traditional irrigation-based chiefdoms of Futuna Island. Further expeditions have taken him to isolated Tikopia, where his excavations exposed stratified sites extending back three thousand years; to Niuatoputapu, a former outpost of the Tongan maritime empire; to Mangaia, with its fortified refuge caves; and to Mo'orea, where chiefs vied to construct impressive temples to the war god 'Oro. In Hawai'i, Kirch traced the islands' history in the Anahulu valley and across the ancient district of Kahikinui, Maui. His joint research with ecologists, soil scientists, and paleontologists elucidated how Polynesians adapted to their island ecosystems. Looking back over the past half-century of Polynesian archaeology, Kirch reflects on how the questions we ask about the past have changed over the decades, how archaeological methods have advanced, and how our knowledge of the Polynesian past has greatly expanded.